Investigation of Altered Spontaneous Brain Activities in Patients With Moyamoya Disease Using Percent Amplitude of Fluctuation Method: A Resting-State Functional MRI Study - Li, Chu-Qi; Ge, Qian-Min; Shu, Hui-Ye; Liao, Xu-Lin; Pan, Yi-Cong; Wu, Jie-Li; Su, Ting; Zhang, Li-Juan; Liang, Rong-Bin; Shao, Yi; Zeng, Er-Ming (Frontiers in Neurology, 2021)
Abstract Background: Moyamoya disease (MMD) is a chronic progressive cerebrovascular abnormality characterized by chronic occlusion of large intracranial vessels with smoky vascular development at the base of the skull. In patients with MMD, abnormal spontaneous brain activity would be expected. Purpose: To assess the brain activity changes in MMD sufferers by resting-state functional magnetic resonance imaging (rs-fMRI), using the percent amplitude of fluctuation (PerAF) analysis method. Materials and methods: 17 MMD patients (3 male and 14 female) and 17 healthy control (HC) subjects with matched gender and age were recruited for this study. We used rs-fMRI to scan all MMD patients. Spontaneous neural activity was evaluated using the PerAF approach. Receiver operating characteristic (ROC) curve analysis was used to assess the ability of PerAF to distinguish MMD patients from HCs. Hospital Anxiety and Depression Scale (HADS) tests were performed to assess the emotional status of MMD patients, and retinal nerve fiber layer thickness (RNFLT) was measured using high-resolution optical coherence tomography (hr-OCT). The relationship between HADS scores, RNFLT values and PerAF signals were assessed using Pearson’s correlation analysis. Results: Compared with HCs, PerAF signals in MMD patients were decreased in the Frontal_Sup_Medial_R and Precentral_L, whereas those in the Caudate_L were increased. The areas under the ROC curves indicated that signals in these brain regions could distinguish between MMD patients and HCs. The PerAF value of Frontal_Sup_Medial_R was positively correlated with the left and right eye RNFLT values and negatively correlated with the HADS scores. Conclusion: In MMD patients, reduced PerAF signals in the Frontal_Sup_Medial_R, Precentral_L, and Caudate_L may be associated with psychiatric diseases including anxiety and depression, and decreased RNFLT may be associated with ophthalmic complications due to the compression of terminal branches of the internal carotid artery in the retinal fiber layer. PerAF can be used as an effective indicator of ocular complications of MMD and to study the neural mechanism underpinning emotional complications in patients with MMD.